Gas Diffusion Electrodes for Efficient Manufacturing of Chlorine and Other Chemicals. (1st January 2017) - Kintrup, Juergen; Millaruelo, Marta; Trieu, Vinh; Bulan, Andreas; Mojica, Ernesto Silva
Abstract : Electrochemical chlorine production is one of the most energy-intensive processes in the chemical industry. Chlorine producers are interested in sustainable ways of optimizing these processes to reduce their energy consumption and carbon footprint. A significant improvement was made possible by Covestro and its technology partners by using the oxygen reduction reaction (ORR) and a gas diffusion electrode—the oxygen depolarized cathode (ODC)—in the electrolysis process. Energy savings of up to 30% can be achieved with this configuration. Gas diffusion electrodes are also used in fuel cells, and due to ongoing efforts in research and development, they are expected to enable the industrial implementation of new, sustainable electrochemical processes including electrosynthesis, water treatment, power generation, and energy storage.